PENERAPAN KOMPETENSI KEWIRAUSAHAAN DI SMK NEGERI 4 MAKASSAR - Busra Bumbungan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This study aimed to describe the implementation of entrepreneurial competence at SMK Negeri 4 Makassar included technical competence, marketing competence, financial competence and interpersonal competence. The results of the study revealed that (1) the technical competence of entrepreneural at SMK Negeri 4 Makassar was conducted with the character of competency skills. The implementation of this activity was related closely the principal entrepreneurial competence, (2) Entrepreneurship at SMK Negeri 4 Makassar in marketing departement was conducted by seeing the needs of the people at school. It is an attitude of innovation, hard work and motivation and entrepreneurial instincts of the principal in seeing entrepreneurial opportunities will be opened up wider marketplace, (3) Financial competence at SMK Negeri 4 Makassar do with the arrangement of goods and financial reporting . These activities can not be separated from the principal entrepreneurial competence, (4) Communication competence of the principal at SMK Negeri 4 Makassar gave space to build partnership to institutions which could the relezation of the school’s vision and mission and could give benefits to both institutoin, (5) the supporting factors on the implementation of entrepreneural competence at SMK Negeri 4 Makassar were assitance on ADB infestation, coordination from each competency skills, partnership with instution, and clear market. Whereas, the inhibing factors were lack of interest in entrepreneurship for students and lack of time management.